Simplify -2[9 - (x + 7)].

Question

Asked 9/24/2012 11:14:13 AM

Updated 6/21/2014 1:21:35 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/21/2014 1:20:54 PM]

s

ArslanBasit|Points 1865|

IAmSoLame|Points 690|

IAmSoLame|Points 690|

Question

Asked 9/24/2012 11:14:13 AM

Updated 6/21/2014 1:21:35 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/21/2014 1:20:54 PM]

Rating

8

-2[9 - (x + 7)]

= -2[-x + 2]

= 2x - 4

= -2[-x + 2]

= 2x - 4

Added 6/21/2014 1:20:53 PM

This answer has been confirmed as correct and helpful.

8

6(x + y) + (x - y)

= (6x + 6y) + (x - y)

= 7x + 5y

= (6x + 6y) + (x - y)

= 7x + 5y

Added 6/21/2014 1:21:35 PM

This answer has been confirmed as correct and helpful.

Can a blood clot in the brain cause a stroke? User: Macular degeneration can cause tooth loss.

Question

Updated 5/14/2014 12:07:15 AM

2 Answers/Comments

How many terms are in the expression 5m2 - mn + 4n + 7? User: Simplify 11(2x + 3). **Weegy:** 16x^3 is the answer. **User:** Simplify 8(3 - 2x). **Weegy:** x = -14/11 **User:** Simplify 81.56 + n - 2.55. **Weegy:** 81.56 + n - 2.55 = 79.01 + n **User:** Simplify 3x + 3 + 2. **Weegy:** (3x^5z)^5 = (3^5) [x^(5+5)] (z)^5 ; (243) (x^10) (z^5) = 243 x^10 z5 ; So the answer is 243 x^10 z5 **User:** Simplify 2x + x. **Weegy:** It seems there is something wrong with the question you put forward. Please can you check it again before i can give an answer? **User:** Simplify 2x + x. **Weegy:** It seems there is something wrong with the question you put forward. Please can you check it again before i can give an answer? **User:** Simplify -12x + 5x. **User:** Simplify 3x + (-12x) - 5x. **Weegy:** 11x-10 is the answer. **User:** Simplify 5x + 4x + 1. **Weegy:** x = 13 is the answer. 5x - 4x = 23 - 10 then x = 13 **User:** Simplify -3xy3 + 7xy3 + (-xy3) + (-3xy3). **Weegy:** =0 **User:** Simplify 6(x + 2) + 7. **Weegy:** that's not possible! what do you need to know. [s] **User:** Simplify -4(N + 9). **Weegy:** 1/16777216 **User:** Simplify 4n5 + 3.5n5 + (-2.1n5). **Weegy:** 4n^5+3.5n^5+(-2.1n^5)
= 7.5n^5 - 2.1n^5
= 5.4n^5 is the simplified form of 4n5 + 3.5n5 + (-2.1n5) **User:** Simplify (5b)(-3a). (More)

Question

Expert Answered

Updated 6/21/2014 1:28:55 PM

9 Answers/Comments

3x + (-12x) - 5x

= 3x - 12x - 5x

= -9x - 5x

= -14x

= 3x - 12x - 5x

= -9x - 5x

= -14x

Added 6/21/2014 1:26:43 PM

This answer has been confirmed as correct and helpful.

5x + 4x + 1 = 9x + 1

Added 6/21/2014 1:27:05 PM

This answer has been confirmed as correct and helpful.

6(x + 2) + 7 = 6x + 12 + 7 = 6x + 19

Added 6/21/2014 1:27:40 PM

This answer has been confirmed as correct and helpful.

-4(N + 9) = -4N - 36

Added 6/21/2014 1:28:07 PM

This answer has been confirmed as correct and helpful.

(5b)(-3a) = -15ab

Added 6/21/2014 1:28:55 PM

This answer has been confirmed as correct and helpful.

34,563,024

questions answered

There are no comments.